THE INFLUENCE OF TAD ORGANIZER, JOURNAL WRITING STRATEGY, AND WRITING APPREHENSION LEVEL ON RECOUNT WRITING ACHIEVEMENT OF THE TENTH GRADE STUDENTS OF SMA BAKTI IBU 8 PALEMBANG - Kurnia Valentina (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2016)
The Influence of TAD Organizer, Journal Writing Strategy, and Writing Apprehension Level on Recount Writing Achievement of the Tenth Grade Students of SMA Bakti Ibu 8 Palembang Kurnia Valentina Senior High School Bakti Ibu 8, Palembang, South Sumatera kurniav@gmail.com Abstract: This study aimed at investigating whether or not there was a significant difference in recount writing achievement of the tenth grade students of SMA Bakti Ibu 8 Palembang who were taught by using Transition Action Detail (TAD) Organizer and those who were taught by using Journal writing. This study also aimed at investigating whether or not there was significant interaction among the strategy (TAD Organizer and Journal writing), apprehension level and writing achievement. There were 78 students as the sample which were devided into two groups equally. Each of the group consisted of 13 high level apprehension, 13 average level apprehension and 13 low level apprehension students. The levels of apprehension were determined by giving Writing strategy Apprehension Scale (WSAS) questionnaire. Both TAD and Journal group were given a pretest and a posttest . To collect the data, a recount writing test was used. The data obtained were analyzed by using independent t test and two-way ANOVA. The result showed that there was significant difference in writing achievement between TAD and Journal group (mean difference= 4.20, p-value= 0.054) and there was not significant interaction effect of the strategy and the level of apprehension on students’writing achievement. To conclude, TAD Organizer and Journal writing strategies were effective for improving students’ recount writing achievement. Key Words: Recount, Transition Action Detail (TAD), Journal Writing